2016
DOI: 10.3892/etm.2016.3708
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a paclitaxel-eluting metallic stent on rabbit esophagus

Abstract: The use of self-expanding metallic stents (SEMS) is the current treatment of choice for malignant gastrointestinal obstructions. A paclitaxel-eluting metallic SEMS (PEMS) may have an antitumor effect on esophageal tissue. PEMS with 10% paclitaxel or conventional SEMS were inserted into the lower esophagus of rabbits. Following the insertion of the stents for 1, 2, 4 and 6 weeks, the rabbits were sacrificed and the status of the stent insertion was examined, as well as any macroscopic or microscopic mucosal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…The PEMS sustaining released drug for at least 6 weeks and stimulated inflammation. The results were consistent with other studies that local drug delivery may inhibit tumor growth by the sustaining histologic changes [27]. However, the molecular mechanism for PEMS needs to be studied in the future.…”
Section: Discussionsupporting
confidence: 91%
“…The PEMS sustaining released drug for at least 6 weeks and stimulated inflammation. The results were consistent with other studies that local drug delivery may inhibit tumor growth by the sustaining histologic changes [27]. However, the molecular mechanism for PEMS needs to be studied in the future.…”
Section: Discussionsupporting
confidence: 91%
“…This kind of localized sustained delivery system in combination with the stent appeared to be a promising strategy to treat malignant esophagus cancer. Fan et al used rabbit esophageal cancer models to evaluate the efficiency and safety of paclitaxel-eluting SEMS [53]. Paclitaxel is currently being used to treat several types of cancer including esophageal carcinoma [54], through inhibiting tumor growth by binding to β -tubulin and stabilizing polymerized microtubules [50, 55].…”
Section: Self-expandable Stentsmentioning
confidence: 99%
“…The new development of this type of drug-eluting stent was a series of new films featuring multilayered structures for improved mechanical properties and unidirectional, controlled drug release [56, 58]. These studies aimed at solving the problem of drug leaking to the stomach through the cannula of stent and esophagus, because a drug-eluting film covering on a SEMS may lack the unidirectional drug release control to target the mucosa tissue of the esophagus [53]. Drugs from the thin film were released to the stomach through the mesh into the canal of the stent, which compromises the drug delivery efficacy of the drug-eluting SEMS and significantly increases side effects.…”
Section: Self-expandable Stentsmentioning
confidence: 99%
“…54 Zhang et al reported the effects of paclitaxel-eluting metallic stent (PEMS) in normal esophagus and in a rabbit esophageal squamous carcinoma model in their serial studies. 55,56 Their results showed that PEMS slowed tumor growth and thereby can serve as an alternative tool for esophageal cancer. However, the molecular mechanism of the antitumor effect was not clear in their study.…”
Section: Drug-eluting Stentsmentioning
confidence: 99%